Pengaruh Faktor Sosial Masyarakat Terhadap Intensitas Kegiatan Keagamaan Islam di Desa Cinta Raja Kabupaten Langkat - Ginting, Rama Noprialdi; Yafizham, Faridah; Ardianti, Septi; Artanti, Nur Raviqah; Ritonga, Rohani; Masdaliva, Fita (Jurnal Abdi Mas Adzkia, 2024)
This study examines the influence of social factors on the intensity of Islamic religious activities in Cinta Raja Village, Langkat Regency. The decline in participation in religious activities, such as congregational prayer and religious studies, is the main focus due to changes in the type of work that requires irregular hours and shifts in the priorities of the younger generation who are exposed to technology. The purpose of the study was to identify social factors that influence community involvement in religious activities and evaluate the KKN strategy implemented to increase participation. The results showed that training strategies, organizing religious events, and religious mentoring succeeded in increasing community participation and showed that appropriate interventions can overcome the challenges of maintaining the intensity of religious activities in the modern era. The conclusion of the study emphasizes the importance of community support and programs that are in accordance with local needs toachieve optimal results in increasing religious activities.